Komplementarność celibatu kapłańskiego i życia małżeńsko-rodzinnego. Refleksja teologiczna - Bartoszek, Antoni (Śląskie Studia Historyczno-Teologiczne, 2010)
This article tries to find the answer to the question on mutual complementarity of charism of virginity and sacrament of matrimony, provided that charism of virginity is narrowed to clerical celibacy. Presenting, at first place of social context, the approach both to matrimony and clerical celibacy as well, it enabled to notice that at present these two institutions are misunderstood, questioned and non-accepted by many people. That is why it was necessary to remind the basic issues of matrimony which are love and life, and for believers it is a sacrament, and also fundamental meanings of clerical celibacy, namely Christological, ecclesiological and eschatological aspects. Further analyses showed in what way marriage and family life constitutes a base and support for clerical celibacy. It is married couples and families who show, by their lives, the priests – celibates what deep love-agape and responsible care for life are. The last part of the article displays that clerical celibacy has essential influence on spiritual and moral lives of married couples and families, it mainly happens by showing spouses and families the person of Jesus Christ, by deeper understanding of Church community and by reminding of bringing men to eternal life.